DEVELOPMENT OF “X-MATH” GAME-BASED LEARNING MEDIA TO INCREASE STUDENT’S MATHEMATICS LEARNING INTEREST - Eka Maya Septianing; M. Ivan Ariful Fathoni; Anisa Fitri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
The decline in students' interest in learning mathematics due to the lack of variety in teaching media used in learning results in low student learning outcomes. One of these problems occurred in class VIII students at SMP Negeri 2 Bojonegoro. There are still educators who only focus on books when learning. Besides, educators who deliver material, especially Cartesian coordinates, only use a whiteboard. The use of this media is certainly not optimal if implemented in continuous learning because apart from spending a lot of time just drawing, it also results in monotonous and boring classes. Therefore, this research aims to develop X-MATH learning media, which is the application of game-based learning to class VIII Cartesian coordinate material that meets valid and practical criteria to increase students' interest in learning. This research uses the Borg and Gall model, which only carries out seven of the ten stages of the development procedure. The research results show that material expert validation results obtained a percentage of 95%, while media validation results obtained a percentage of 91.6%. Both results meet the level of validity, namely very valid and suitable for use. Besides that, based on field trials conducted with mathematics educator respondents and students, the average score percentage was 83.3%, so the media was categorized as quite practical. Based on the results of this research, the game-based X-MATH learning media developed is very valid and quite practical to use in learning Cartesian coordinates. Turunnya minat belajar matematika peserta didik yang disebabkan kurang bervariasinya media ajar yang digunakan dalam pembelajaran mengakibatkan rendahnya hasil belajar peserta didik. Permasalahan ini terjadi salah satunya pada peserta didik kelas VIII SMP Negeri 2 Bojonegoro. Masih dijumpai pendidik yang hanya terfokus pada buku saat pembelajaran. Selain itu, pendidik dalam penyampaian materi khususnya koordinat kartesius bahan ajar yang digunakan hanya papan tulis. Penggunaan media tersebut tentu kurang optimal jika dimplementasikan dalam pembelajaran berkelanjutan karena selain menghabiskan banyak waktu hanya untuk menggambar juga mengakibatkan kelas monoton dan membosankan. Sebab itu, tujuan dari penelitian ini adalah mengembangkan media pembelajaran X-MATH yang merupakan penerapan dari pembelajaran berbasis game pada materi koordinat kartesius kelas VIII yang memenuhi kriteria valid dan praktis guna meningkatkan minat belajar peserta didik. Penelitian ini merupakan penelitian pengembangan menggunakan model Borg and Gall yang hanya melaksanakan tujuh dari sepuluh tahapan prosedur pengembangan. Hasil penelitian menunjukkan bahwa hasil validasi ahli materi memperoleh persentase sebesar 95%, sedangkan hasil validasi media memperoleh persentase sebesar 91,6%. Kedua hasil tersebut memenuhi tingkat validitas yaitu sangat valid dan dapat digunakan. Selain itu, berdasarkan uji coba lapangan yang dilakukan dengan responden pendidik matematika dan peserta didik menghasilkan persentase skor rata-rata sebesar 83,3% sehingga media dikategorikan cukup praktis. Berdasarkan hasil penelitian tersebut maka media pembelajaran X-MATH berbasis game yang dikembangkan sangat valid dan cukup praktis digunakan dalam pembelajaran koordinat kartesius.